Factors influencing workplace accidents among construction workers at Carita Sdn Bhd, Desa Aman Puri, Kepong, Selangor / Nurazlinda Zolkepre - Zolkepre, Nurazlinda (Faculty of Business and Management, 2020)
Construction industry recognize as a high hazard and riskiest industry that comprises a wide range of activities that involving construction, alteration or repair. Construction workers engage in many activities that may expose them into serious hazards, such as falling from rooftops, unguarded machinery and being struck by heavy construction equipment at construction site. The fatality rate that involve construction workers keep worrying many parties especially every construction company. There are so many cases of accidents in construction industries were reported by Department of Occupational Safety and Health involving construction workers. This situation keep worrying every construction company since the project at the construction site cannot be finish according to the time because the project must be postponed because of accidents that happen. The purpose of this study is to identify the most influence factor that can contribute to workplace accidents among construction workers. The study will focus on construction project in Malaysia. The study will also emphasize on how unsafe act, stress and fatigue, lack of training procedures and not aware on personal protective equipment will contribute to the accidents at the construction site. The results from the questionnaires that get from the 97 respondents will be analyse by using Cronbach’s Alpha using Statistical Package for the Social Sciences (SPSS) software. Based on the result, it can be conclude that elements like unsafe act, stress and fatigue and Personal Protective Equipment assumed to directly influence to workplace accidents among construction workers.